HDV seroprevalence in hbsag-positive patients in china occurs in hotspots and is not associated with HCV mono-infection - Roggenbach, Imme; Chi, Xiumei; Lempp, Florian A.; Qu, Bingqian; Walter, Lisa; Wu, Ruihong; Gao, Xiuzhu; Schnitzler, Paul; Ding, Yanhua; Urban, Stephan; Niu, Junqi (Viruses, 2021)
HDV infection causes severe liver disease, the global health burden of which may be underestimated due to limited epidemiological data. HDV depends on HBV for infection, but recent studies indicated that dissemination can also be supported by other helper viruses such as HCV. We used a rapid point-of-care test and an ELISA to retrospectively test for antibodies against the Hepatitis Delta antigen (anti-HDV-Ab) in 4103 HBsAg-positive and 1661 HBsAg-negative, anti-HCV-positive sera from China and Germany. We found that the HDV seroprevalence in HBsAg-positive patients in China is limited to geographic hotspots (Inner Mongolia: 35/251, 13.9%; Xinjiang: 7/180, 3.9%) and high-risk intravenous drug users (HBV mono-infected: 23/247, 9.3%; HBV-HCV co-infected: 34/107, 31.8%), while none of the 2634 HBsAg carriers from other metropolitan regions were anti-HDV-Ab-positive. In Germany, we recorded an HDV seroprevalence of 5.3% in a university hospital environment. In a cohort of HBsAg-negative, anti-HCV-positive patients that were not exposed to HBV before (anti-HBc-negative), HDV was not associated with HCV mono-infection (Chinese high-risk cohort: 0/365, 0.0%; German mixed cohort: 0/263, 0.0%). However, 21/1033 (2.0%) high-risk HCV patients in China with markers of a previously cleared HBV infection (anti-HBc-positive) were positive for anti-HDV-Ab, with two of them being positive for both HDV and HCV RNA but negative for HBV DNA. The absence of anti-HDV-Ab in HCV mono-infected patients shows that HCV cannot promote HDV transmission in humans.